Mild cognitive impairment with Lewy bodies: blood perfusion with arterial spin labelling - Firbank, Michael J. (J Neurol, 2020)
OBJECTIVE: To use arterial spin labelling to investigate differences in perfusion in mild cognitive impairment with Lewy bodies (MCI-LB) compared to Alzheimer type MCI (MCI-AD) and healthy controls. METHODS: We obtained perfusion images on 32 MCI-LB, 30 MCI-AD and 28 healthy subjects of similar age. Perfusion relative to cerebellum was calculated, and we aimed to examine differences in relative perfusion between MCI-LB and the other groups. This included whole brain voxelwise comparisons, as well as using predefined region-of-interest ratios of medial occipital to medial temporal, and posterior cingulate to precuneus. Differences in occipital perfusion in eyes open vs eyes closed conditions were also examined. RESULTS: Compared to controls, the MCI-LB showed reduced perfusion in the precuneus, parietal, occipital and fusiform gyrus regions. In our predefined regions, the ratio of perfusion in occipital/medial temporal was significantly lower, and the posterior cingulate/precuneus ratio was significantly higher in MCI-LB compared to controls. Overall, the occipital perfusion was greater in the eyes open vs closed condition, but this did not differ between groups. CONCLUSION: We found patterns of altered perfusion in MCI-LB which are similar to those seen in dementia with Lewy bodies, with reduction in posterior parietal and occipital regions, but relatively preserved posterior cingulate.